2008
DOI: 10.1007/s11858-008-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and interdisciplinarity: one creativity or many creativities?

Abstract: Psychologists and educators frequently debate whether creativity and problem solving are domain-general-applicable to all disciplines and tasks-or domainspecific-tailored to specific disciplines and tasks. In this paper, we briefly review the major arguments for both positions, identify conceptual and empirical weaknesses of both perspectives, and describe two relatively new hybrid models that attempt to address ways in which creativity and innovation are both domain-general and domain-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 37 publications
0
15
0
7
Order By: Relevance
“…Although popular belief of eureka moments remains, most discoveries are through systematic research and work (Sawyer 2006), which is also the case for interdisciplinary research. Plucker and Zabelina (2009) found weaknesses in conceptualising creativity as either domain (or disciplinary)-specific or domain-general, and argue for a hybrid position. Sill (1996) developed a widely-used notion of creativity that serves as a model for synthesis and integrative thought, and a foundation for Interdisciplinary Studies fields.…”
Section: Interdisciplinary Perspectivesmentioning
confidence: 99%
“…Although popular belief of eureka moments remains, most discoveries are through systematic research and work (Sawyer 2006), which is also the case for interdisciplinary research. Plucker and Zabelina (2009) found weaknesses in conceptualising creativity as either domain (or disciplinary)-specific or domain-general, and argue for a hybrid position. Sill (1996) developed a widely-used notion of creativity that serves as a model for synthesis and integrative thought, and a foundation for Interdisciplinary Studies fields.…”
Section: Interdisciplinary Perspectivesmentioning
confidence: 99%
“…The insight problem‐solving approach also does not differentiate between different types of creativity, assuming creativity is either all or none. However, beginning in the 1990s, growing evidence has supported the existence of domain‐specific creativity (Baer, ; Kaufman & Baer, ; Plucker & Zabelina, ). In particular, research has revealed three major types of creativity based on self‐ratings (Kaufman & Baer, ; Oral, Kaufman & Agars, ): Artistic/Bodily (‘hands‐on’ creativity in art, craft, and bodily/physical creativity), Math/Science (creativity in math and science), and Writing/Communication (creativity in interpersonal relationships, communication, and writing).…”
Section: Introductionmentioning
confidence: 97%
“…An increased knowledge of these personal attributes makes it possible to elaborate programs that strive for the development of those abilities, that allow for the discovery of barriers that prevent its expression and foment the development of creative potential (Plucker & Zabelina, 2009).…”
mentioning
confidence: 99%